A simple model for penetration of aerosols in bifurcating tubes - Miguel, A. F. (2021)
Aerosol dynamics within bifurcating tubes is important due to the health risks associated with inhaled aerosols, but also due to pharmacological drug delivery which helps the treatment of systemic diseases in a non-invasive and effective way [1]. There is a bonded link between aerosol flows, geometric configuration of tubes and deposition of aerosols. Aerosols within bifurcating tubes follow paths during that several processes may influence their deposition. Interception is an important deposition mechanism for elongated aerosols [2,3]. Although, for large particles (diameter larger than 0.5 μm) deposition by impaction occurs because aerosols cannot follow the air streamlines, diffusion deposition is important for small particles (diameter less than 0.2 μm) [1-3]. In small tubes, deposition by sedimentation is a very important deposition mechanism. The goal of the present research is to study the penetration of aerosols in bifurcating tubes which deposition occurs by the combined action of sedimentation and diffusion mechanisms. A model is developed which assumes that aerosols move with the mean fluid velocity, and the particle loss is obtained from empirical coefficients of efficiency available in the literature.